Peran Diaspora Arab di Indonesia: Jejak Perdagangan, Islamisasi, Pendidikan, dan Budaya di Gresik Sejak Abad XIX - Diva Putri Prahesti (Jurnal Sejarah Indonesia, 2025)
The purpose of this study is to explain the contributions made by the Arab diaspora in Gresik, Indonesia, over the years in various fields, including trade, Islamization, education, and culture. Gresik, a major trading center on the north coast of Java, attracted an Arab community, which contributed significantly to the region's social and economic progress. This article uses archival sources and historical research with a literature review approach to demonstrate that the Arab diaspora not only strengthened global trade networks but also contributed to the spread of Islam by building mosques and educational institutions. Furthermore, the Arab presence in Gresik also left a deep impression on the area's social and cultural landscape, as seen in art, architecture, and customs. This study demonstrates that the contribution of the Arab diaspora has been a significant factor in shaping Gresik's distinctive local identity, which remains to this day.